Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to evaluate the closed-forms of series

\begin{equation} 1)\,\, \sum_{n=0}^\infty\frac{1}{(3n)!}\qquad\left|\qquad2)\,\, \sum_{n=0}^\infty\frac{1}{(3n+1)!}\qquad\right|\qquad3)\,\, \sum_{n=0}^\infty\frac{1}{(3n+2)!}\\ \end{equation}

Of course Wolfram Alpha can give us the closed-forms \begin{align} \sum_{n=0}^\infty\frac{1}{(3n)!}&=\frac{e}{3}+\frac{2\cos\left(\frac{\sqrt{3}}{2}\right)}{3\sqrt{e}}\\ \sum_{n=0}^\infty\frac{1}{(3n+1)!}&=\frac{e}{3}+\frac{2\sin\left(\frac{\sqrt{3}}{2}-\frac{\pi}{6}\right)}{3\sqrt{e}}\\ \sum_{n=0}^\infty\frac{1}{(3n+2)!}&=\frac{e}{3}-\frac{2\sin\left(\frac{\sqrt{3}}{2}+\frac{\pi}{6}\right)}{3\sqrt{e}} \end{align} but how to get those closed-forms by hand? I can only notice that \begin{equation} \sum_{n=0}^\infty\frac{1}{n!}=\sum_{n=0}^\infty\frac{1}{(3n)!}+\sum_{n=0}^\infty\frac{1}{(3n+1)!}+\sum_{n=0}^\infty\frac{1}{(3n+2)!}=e \end{equation} Could anyone here please help me? Any help would be greatly appreciated. Thank you.

PS: Please don't work backward.

share|improve this question
I believe this link might prove itself helpful. –  Lucian Aug 30 at 18:54
Thank you Mr. @Lucian. BTW, where did you get those formulas? –  Anastasiya-Romanova Aug 30 at 18:58

4 Answers 4

up vote 3 down vote accepted

Related techniques: (I). Here is an approach which enables you to tackle your problems. Let's consider the series

$$ f(x) = \sum_{n=0}^{\infty}\frac{x^{3n}}{(3n)!}. $$

Taking the Laplace transform gives

$$ F(s) = \sum_{n=0}^{\infty}\frac{1}{s^{3n+1}} = \frac{s^2}{s^3-1}. $$

To finish the problem you need to find the inverse Laplace of $F(s)$. One technique is partial fraction

$$ F(s) = \frac{1}{3(s-1)} + \frac{1}{3(s+1/2-i\sqrt{3}/2)} + \frac{1}{3(s+1/2+i\sqrt{3}/2)} .$$


1) Laplace transform is defined as

$$ F(s) = \int_{0}^{\infty}f(x)e^{-sx}dx. $$

2) Laplace transform of $x^m$ is

$$ \frac{\Gamma(m+1)}{s^{m+1}} $$

3) Laplace transform of $e^{ax}$ is

$$ \frac{1}{s-a}. $$

Or equivalently the inverse Laplace of $\frac{1}{s-a}$ is $e^{ax}$

$$ $$

share|improve this answer
It seems hard to me. I haven't learnt Laplace transform yet. +1 anyway. Thank you. –  Anastasiya-Romanova Aug 30 at 19:25
@V-Moy: It is not hard to learn. You are welcome. –  Mhenni Benghorbal Aug 30 at 19:27
@V-Moy: See what I added. –  Mhenni Benghorbal Aug 30 at 19:30
OK, thanks. I'll learn it. –  Anastasiya-Romanova Aug 30 at 19:39
I think I understand the concept of Laplace transform. Let \begin{equation} f(x)=\sum_{n=0}^\infty \frac{x^m}{m!} \end{equation} where $m=an+b$. Multiplying both sides by $e^{-px}$, then integrating \begin{align} \int_0^\infty f(x)e^{-px}\,dx&=\sum_{n=0}^\infty \int_0^\infty\frac{x^m}{m!}e^{-px}\,dx\\ F(p)&=\sum_{n=0}^\infty\frac{1}{p^{m+1}}\\ &=\sum_{n=0}^\infty\frac{1}{p^{an+b+1}}\\ &=\frac{p^{a-b-1}}{p^{a}-1}\\ \end{align} then to get $f(x)$ we use the inverse of $F(p)$, right? –  Anastasiya-Romanova Aug 30 at 20:26

Another possible approach is to use the discrete Fourier transform. Let $\omega=\exp\frac{2\pi i}{3}$. Then: $$f(n)=\frac{1}{3}\left(1+\omega^n+\omega^{2n}\right)=\mathbb{1}_{n\equiv 0\!\pmod{3}}(n),$$ hence: $$\color{red}{\sum_{n=0}^{+\infty}\frac{1}{(3n)!}}=\sum_{n=0}^{+\infty}\frac{f(n)}{n!}=\frac{1}{3}\left(\exp(1)+\exp(\omega)+\exp(\omega^2)\right)=\color{red}{\frac{e}{3}+\frac{2}{3\sqrt{e}}\cos\frac{\sqrt{3}}{2}.}$$ The other two series can be computed with the same technique, by noticing that: $$f_1(n)=\frac{1}{3}\left(1+\omega^2\cdot\omega^n+\omega\cdot\omega^{2n}\right)=\mathbb{1}_{n\equiv 1\!\pmod{3}}(n),$$ $$f_2(n)=\frac{1}{3}\left(1+\omega\cdot\omega^n+\omega^2\cdot\omega^{2n}\right)=\mathbb{1}_{n\equiv 2\!\pmod{3}}(n).$$

share|improve this answer
Oh Lord, the previous answer is using Laplace transform and this one is using Fourier transform. Does 'transform' stand for transformation? If so, how many transformation are there in math? BTW, +1 Mr. D'Aurizio. –  Anastasiya-Romanova Aug 30 at 19:45

$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ With $\ds{\ell = 0,1,2}$:

\begin{align} {\cal I}_{\ell}&\equiv\sum_{n = 0}^{\infty}{1 \over \pars{3n + \ell}!}= \sum_{n = 0}^{\infty}\sum_{k=0}^{\infty}{\delta_{k,3n + \ell} \over k!} =\sum_{n,k = 0}^{\infty}{1 \over k!} \oint_{\atop{\atop\verts{z}\ =\ a\ >\ 1}}{1 \over z^{3n + \ell - k + 1}} \,{\dd z \over 2\pi\ic} \\[3mm]&=\oint_{\atop{\atop\verts{z}\ =\ a\ >\ 1}}{1 \over z^{\ell + 1}} \bracks{\sum_{n = 0}^{\infty}\pars{1 \over z^{3}}^{n}} \bracks{\sum_{k = 0}^{\infty}{z^{k} \over k!}}\,{\dd z \over 2\pi\ic} \\[3mm]&=\oint_{\atop{\atop\verts{z}\ =\ a\ >\ 1}}{1 \over z^{\ell + 1}} \,{1 \over 1 - 1/z^{3}}\,\expo{z}\,{\dd z \over 2\pi\ic} =\oint_{\atop{\atop\verts{z}\ =\ a\ >\ 1}} {z^{2 - \ell} \over z^{3} - 1}\,\expo{z}\,{\dd z \over 2\pi\ic} \\[3mm]&=\sum_{m = -1}^{1}{z_{m}^{2 - \ell}\expo{z_{m}} \over 3z_{m}^{2}}\qquad \mbox{where}\qquad z_{m} \equiv \exp\pars{2m\pi\ic \over 3}\,,\quad m = -1,0,1 \end{align}

Then, \begin{align} {\cal I}_{\ell} &= {1 \over 3} \sum_{m = -1}^{1}z_{m}^{-\ell}\expo{z_{m}} ={1 \over 3}\,\expo{} + {2 \over 3}\,\Re\pars{z_{1}^{-\ell}\expo{z_{1}}} ={1 \over 3}\,\expo{} +{2 \over 3}\,\Re\pars{\expo{-2\ell\pi\ic/3}\exp\pars{\expo{2\pi\ic/3}}} \\[3mm]&={1 \over 3}\,\expo{} +{2 \over 3}\, \Re\pars{\expo{-2\ell\pi\ic/3}\exp\pars{-\,\half + {\root{3} \over 2}\,\ic}} \\[3mm]&={1 \over 3}\,\expo{} +{2 \over 3\root{\expo{}}}\, \Re\exp\pars{\bracks{{\root{3} \over 2} - {2\pi \over 3}\,\ell}\ic} \end{align}

$$ {\cal I}_{\ell}\equiv\sum_{n = 0}^{\infty}{1 \over \pars{3n + \ell}!} ={1 \over 3}\,\expo{} +{2 \over 3\root{\expo{}}}\,\cos\pars{{\root{3} \over 2} - {2\pi \over 3}\,\ell} \,,\qquad\ell = 0,1,2 $$

$$\begin{array}{rclcl} {\cal I}_{0}&=&\color{#66f}{\large\sum_{n = 0}^{\infty}{1 \over \pars{3n}!}} &=&{1 \over 3}\,\expo{} +{2 \over 3\root{\expo{}}}\,\cos\pars{{\root{3} \over 2}} \\[5mm] {\cal I}_{1}&=&\color{#66f}{\large\sum_{n = 0}^{\infty}{1 \over \pars{3n + 1}!}} &=&{1 \over 3}\,\expo{} +{2 \over 3\root{\expo{}}}\ \overbrace{\cos\pars{{\root{3} \over 2} - {2\pi \over 3}}} ^{\ds{\color{#c00000}{\sin\pars{{\root{3} \over 2} - {\pi \over 6}}}}} \\[5mm] {\cal I}_{2}&=&\color{#66f}{\large\sum_{n = 0}^{\infty}{1 \over \pars{3n + 2}!}} &=&{1 \over 3}\,\expo{} +{2 \over 3\root{\expo{}}}\ \underbrace{\cos\pars{{\root{3} \over 2} - {4\pi \over 3}}} _{\ds{\color{#c00000}{-\sin\pars{{\root{3} \over 2} + {\pi \over 6}}}}} \end{array} $$

share|improve this answer
Although I don't understand your approach but +1 Mr. Marin. Thanks for providing me the general formula for my OP. ≧◠◡◠≦✌ –  Anastasiya-Romanova Aug 31 at 13:22

This problem can be solved without advanced techniques. We have the Taylor series $$ e^x = \sum_{n\geq 0} \frac{x^n}{n!}. $$ As the questioner noted, plugging $x=1$ yields the equation $A+B+C=e$ connecting the three unknown sums. However, plugging in any cube root of unity also sheds light on the question because the numerators $x^n$ will repeat with period $3$. Let $\omega = e^{2\pi i/3}$; plugging $x = \omega$ yields $A + \omega B + \omega^2 C = e^{\omega}$, and plugging $x = \omega^2$ yields $A + \omega^2 B + \omega C = e^{\omega^2}$. We now have three equations that can be solved easily for the three unknowns $A$, $B$, and $C$. For instance, adding all three equations together yields $$ 3A = e + e^\omega + e^{\omega^2} = e + e^{-1/2}\left(\cos \frac{\sqrt{3}}{2} + i \sin \frac{\sqrt{3}}{2}\right) + e^{-1/2}\left(\cos \frac{-\sqrt{3}}{2} + i \sin \frac{-\sqrt{3}}{2}\right) $$ $$ = e + \frac{2}{\sqrt{e}} \cos \frac{\sqrt{3}}{2}, $$ in accordance with Wolfram Alpha.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.